Jual Beli Tanah Di Sandbox Metaverse Dalam Perspektif Hukum Ekonomi Syariah - Wati, Ai; Hakim, Iman Lukmanul (Jurnal Hukum Ekonomi Syariah, 2023)
Along with the development of an increasingly sophisticated technological era, several aspects of life are increasingly attached to technology, one of which is buying and selling. Evidence of technological progress is the existence of a new world online, which builds a virtual world called Metaverse. “Metaverse is a social aspect, game, augmented reality (AR), virtual reality (VR), and digital currency that allows individuals to interact with each other virtually, one of which is the Metaverse is Sandbox. Just like in the real world, we can buy and sell land virtually in the Metaverse Sandbox, where the land can be an investment and a potential price increase, but behind that it has a risk, namely when this platform goes out of business, it could lose that value. The formulation of the problem in this research is: What is the mechanism for buying and selling land in Sandbox Metaverse? Also, what is the perspective of sharia economic law regarding buying and selling land in Sandbox Metaverse? So this study aims to determine the buying and selling of land in Sandbox Metaverse in the perspective of sharia economic law. This research is included in the type of qualitative research by approaching it with interview techniques, literature and documentation. The data was analyzed through the stages of data reduction, data presentation, then drawing conclusions. Based on the results of this study, the sale and purchase of land in the Sandbox Metaverse, which is then correlated with the theory of sharia economic law and the sale and purchase theory of assets, the sale and purchase has fulfilled the pillars and conditions for the formation of the contract, but the perfecting element in the object of the contract is not fulfilled from a technical point of view so that the contract becomes facades, and land in Sandbox Metaverse are included in intangible assets. Keywords: Sharia Economic Law, Buying and Selling, Metaverse, Sandbox, Virtual Land, Assets